Association of EPCR Polymorphism rs867186-GG With Severity of Human Malaria - Cespedes, Juan Carlos; Hibbert, Jacqueline; Krishna, Sri; Yan, Fengxia; Bharti, Praveen K.; Stiles, Jonathan K.; Liu, Mingli (Frontiers in Genetics, 2020)
Background: Cerebral malaria (CM) is characterized by the sequestration of Plasmodium-infected erythrocytes (pRBCs) to host brain microvasculature beds via P. falciparum erythrocyte membrane protein 1 (PfEMP1). Under normal conditions, activated protein C (APC) bound to endothelial protein C receptor (EPCR) has cytoprotective properties via the activation of protease-activated receptor 1 (PAR1). During malaria infection, pRBCs transports PfEMP1 to the membranes to bind EPCR in the same region as APC. As a result, APC is less capable of inducing cytoprotective effects via PAR1. Two studies involving adult malaria patients revealed that EPCR rs867186-GG allele is associated with protection against severe malaria, while three other studies involving children malaria patients could not show association between EPCR rs867186-GG allele and severe malaria or increased mortality among children with CM. Methods: We examined whether or not the EPCR rs867186-GG allele protects against cerebral malaria. Peripheral blood samples were collected from 47 malaria patients and four healthy individuals from a study conducted from 2004 to 2007 at the NSCB Medical College Hospital in India. CM and malaria-associated complications were defined based on WHO criteria. Genomic DNA was isolated from the peripheral blood mononuclear cells. Primer sequences were designed to contain rs867186 of the PROCR gene (NM 006404) and were used to amplify a 660 bp product as described before [1]. PCR products were purified, and DNA sequences were determined by Sanger Sequencing (www.Genewiz.com. Genewiz, NJ). Nonparametric tests were used to compare the groups. To analyze differences in allele frequencies, we used chi-squared or Fisher’s exact tests for categorical variables if the expected values were less than 5. P-value <0.05 was considered statistically significant. Results: Our results showed significantly higher rates of AG and GG in CM patients compared to mild malaria (P = 0.0034); similarly, there are significantly higher rates of AG in CM patients compared to mild malaria patients (P = 0.0017). Conclusion: Our results indicate that rs867186-GG or rs867186-AG genotypes are not associated with protection against HCM.